EXPERIENCE TREATMENT OF CHILDREN WITH POST-BURN SCAR CONTRACTURE OF THE NECK - V. V. Perlovskaya; V. N. Zelenin; I. B. Li; L. V. Angarkhaeva (Acta Biomedica Scientifica)
Cicatricial deformations of the neck occur in 4-30.5 % of children suffered from burn trauma, and are the most severe consequences. Early reconstructive surgery in this pathology provides free growth and development of the skull and upper body and promote psychological and social recovery of the child. The treatment of such patients presents great difficulties, and in each case requires an individual approach. The article presents the experience of treatment of two children with severe scar contracture of the neck, complicated by the lack of reserves in undamaged tissues of the neck and the surrounding areas. We used a combination of several methods of skin grafting, including axial flow and the prefabrication of flaps, divided in time into stages. In one case in a child with total neck contracture, we performed pre-surgical (3.5 weeks before the main stage surgical intervention) preparation of the two flaps - scapular and epaulet flaps. In the other case, 4-year old girl with subtotal flexion contracture, a month before the main surgery we prepared scapular flap and increased its area expander dermotension, with endoscopic implantation of endoexpander. In this paper, we describe in detail the technology of operative treatment of these two patients. In both cases, there were no postoperative complications. The use of modern medical technologies based on conventional techniques in surgical correction of severe flexion scar contractures of the neck of the presented patients decided both functional and aesthetic problems.